Longitudinal diffusion changes following postoperative delirium in older people without dementia - Cavallari, Michele (Neurology, 2017)
OBJECTIVE: To investigate the effect of postoperative delirium on longitudinal brain microstructural changes, as measured by diffusion tensor imaging. METHODS: We studied a subset of the larger Successful Aging after Elective Surgery (SAGES) study cohort of older adults (≥70 years) without dementia undergoing elective surgery: 113 participants who had diffusion tensor imaging before and 1 year after surgery. Postoperative delirium severity and occurrence were assessed during the hospital stay using the Confusion Assessment Method and a validated chart review method. We investigated the association of delirium severity and occurrence with longitudinal diffusion changes across 1 year, adjusting for age, sex, vascular comorbidity, and baseline cognitive performance. We also assessed the association between changes in diffusion and cognitive performance across the 1-year follow-up period, adjusting for age, sex, education, and baseline cognitive performance. RESULTS: Postoperative delirium occurred in 25 participants (22%). Delirium severity and occurrence were associated with longitudinal diffusion changes in the periventricular, frontal, and temporal white matter. Diffusion changes were also associated with changes in cognitive performance across 1 year, although the cognitive changes did not show significant association with delirium severity or occurrence. CONCLUSIONS: Our study raises the possibility that delirium has an effect on the development of brain microstructural abnormalities, which may reflect brain changes underlying cognitive trajectories. Future studies are warranted to clarify whether delirium is the driving factor of the observed changes or rather a correlate of a vulnerable brain that is at high risk for neurodegenerative processes.